Antibiotic susceptibility of wound isolates in plastic surgery patients at a tertiary care centre - Surendra B. Patil; Amit Paramne; Shree Harsh (Indian Journal of Plastic Surgery)
Context: Wound infection increases the hospital stay and adversely affects the recovery of patients. Culture and sensitivity of wound isolates help in proper diagnosis and management of these patients. Aim: To identify common bacteria causing wound infections and their antibiotic sensitivity pattern. Study Design: A cross-sectional study. Place and Duration of Study: Government Medical College and Hospital, Nagpur from October 2013 to October 2015. Materials and Methods: Pus samples were collected by doctors in ward using Sterile Swab Sticks. Bacterial isolates were identified and cultured, and antibiotic culture sensitivity tests were performed. Statistical Analysis Used: Chi-square test. Results: There were a total of 150 patients with infected wounds. Most common organism isolated was Pseudomonas followed by Klebsiella and Staphylococcus aureus. All of these organisms were resistant to most routine antibiotics. Conclusion: We suggest a multidisciplinary approach to wound management, rational drug use, routine microbiological surveillance of wounds and institution of hospital infection control policy.